Association between site of lesion and driving performance after ischemic stroke. Issue 4 (August 2015) - Devos, Hannes; Verheyden, Geert; Van Gils, Annick; Tant, Mark; Akinwuntan, Abiodun Emmanuel
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Stroke presents with heterogeneous recovery periods, severity, and manifestation of deficits, all of which may adversely impact fitness-to-drive. Little is known about the association between site of lesion and driving performance after stroke. Objective: To investigate the association between site of stroke lesion and driving performance. Method: Seventy-three participants (age = 56 ± 11 years; 66 men) underwent a detailed battery of visual, cognitive, and on-road tests to determine fitness-to-drive at about 10 months after ischemic stroke. Associations between stroke location and driving performance were calculated using rank biserial (rrb) correlation coefficients. Correlations were considered weak below 0.10, moderate between 0.10 and 0.49, and strong above 0.50. Wilcoxon rank sum tests were employed to discern differences in on-road driving performance between participants whose performance was of concern to the driving assessor and those who exhibited no major difficulties on the road. Results: In all, 28 (38%) out of the 73 participants exhibited major difficulties on the road. Those who showed difficulties on the road performed worse in all driving skills (P < 0.05). Correlation analysis showed moderate to strong correlations between site of lesion and performance in several visual, cognitive and on-road tests. Lesions in the parietal lobe showed correlations ranging between 0.23 and 0.25 with driving skills including vehicle control and speed adaptations. Lesions in the occipital lobes correlated strongly with visual field (rrb = 0.53) and moderately with visual neglect (rrb = 0.28). Conclusions: Our results suggest that cortical lesions in the parietal and occipital lobes are associated with driving deficits after stroke. Further advances in our understanding of the neural correlates of driving performance may provide prognostic markers of fitness-to-drive and lead to early, targeted rehabilitation.